PENGGUNAAN METODE RESITASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS TERPADU TENTANG LETAK GEOGRAFIS DAN KOORDINAT NEGARA ASEAN (Penelitian Tindakan Kelas di Kelas VIII-G SMPN 6 Tasikmalaya) - Rumiati, Eti (Wahana Pendidikan, 2020)
ABSTRACTThe purpose of this study was to determine the use of the recitation method to improve student learning outcomes in social studies learning about Geographical Location and ASEAN Country Coordinates in Class VIII-G of SMPN 6 Tasikmalaya. The research method is Classroom Action Research (PTK). The results of the data analysis showed that the first action learning plan got an average score of 3,35 or 83,75%. Meanwhile, the second action learning plan obtained an average score of 4,00 or 100%. The results of data analysis also showed that the average score of teacher activity in the first action was 3,06 or 76,5%. The second act received an average score of 3,50 or 87,5%. For student activity in the second action the students got an average score of 3,12 or 78%. In the second action got an average score of 3,62 or 90,55%. The results of student learning in each cycle obtained data that in the first action the average value was 79, in the second action it was 84. This means that social studies learning through the recitation method, in addition to influencing the planning and implementation of learning, also has an effect on improving learning outcomes. students.Keywords: recitation method, student learning outcomesABSTRAKTujuan penelitian ini adalah untuk mengetahui penggunaan metode resitasi untuk meningkatkan hasil belajar siswa pada pembelajaran IPS tentang Letak Geografis dan Koordinat Negara ASEAN di Kelas VIII-G SMPN 6 Tasikmalaya. Metode penelitian adalah Penelitian Tindakan Kelas (PTK). Hasil analisis data menunjukkan bahwa Rencana Pelaksanaan Pembelajaran tindakan pertama mendapat skor rata-rata 3,35 atau 83,75%. Sedangkan rencana pembelajaran tindakan kedua memperolah skor rata-rata 4,00 atau 100%. Hasil analisis data juga menunjukkan bahwa skor rata-rata aktivitas guru pada tindakan pertama adalah 3,06 atau 76,5%. Tindakan kedua mendapat skor rata-rata 3,50 atau 87,5%. Untuk aktivitas siswa pada tindakan kedua siswa mendapat skor rata-rata 3,12 atau 78%. Pada Tindakan kedua mendapat skor rata-rata 3,62 atau 90,55%. Hasil belajar siswa pada setiap siklus diperoleh data bahwa pada tindakan pertama nilai rata-rata sebesar 79, pada tindakan kedua sebesar 84. Hal ini dapat diartikan bahwa pembelajaran IPS melalui metode resitasi, selain berpengaruh terhadap rencana dan pelaksanaan pembelajaran, juga berpengaruh terhadap peningkatkan hasil belajar siswa.Kata kunci: metode resitasi, hasil belajar siswa